Development Of Problem-Solving Measuring Instrument In Motion Topic Using the Testlet Model - Haratua Tiur Maria Silitonga; Erwina Oktavianty; Ray Cinthya Habellia (Jurnal Penelitian Pendidikan IPA, 2024)
This research aims to produce the Testlets' model instrument test that measures the problem-solving abilities of high school students in West Kalimantan on motion topics. The study employed A.D.D.I.E.'s development model, which consists of analysis, design, development, implementation, and evaluation stages. Three hundred four students from three different cities in West Kalimantan were involved as respondents in this study. The researchers collected data through test techniques and documentation since this study focused on the characteristics of the test. The instrument test of problem-solving abilities is designed to follow Heller's solution stages, namely focusing on the problem, describing physics, planning a solution, implementing the plan, and evaluating the answer. The results of this study are the availability of 20 multiple-choice questions, with five main questions and four testlets. The assessment instrument developed had the characteristics of validity up to 0.90 (high), reliability through Cronbach's Alpha Reliability analysis: 0.83 (very good), person reliability: 0,84 (high) and item reliability: 0.98 (excellent). The test developed is theoretically and practically feasible so that high school physics teachers can use it to measure students' problem-solving abilities more quickly because it uses a multiple-choice test.